Stage-specific metabolic divergence in flavonoid biosynthesis correlates with embryogenic capacity in rubber tree (Hevea brasiliensis) - Miao, Jia; Sun, Xiao-Long; Liu, Jin; Gui, Ming-Chun; Tang, Min; Tian, Hai; Shi, Wan-Yuan; Li, Ling (Frontiers in Plant Science, 2026)
IntroductionSomatic embryogenesis (SE) is an essential propagation technology for Hevea brasiliensis, yet its application remains limited by the strong genotype dependence of embryogenic capacity.MethodsTo elucidate the metabolic basis of this variation, we conducted integrated metabolomic and transcriptomic analyses across four SE developmental stages in a high-embryogenic (HE) and a low-embryogenic (LE) genotype, including explants, induced callus, non-embryogenic / embryogenic callus, and cotyledonary embryos (HE-specific).ResultsA total of 1,383 metabolites belonging to 11 major classes were identified, with flavonoids, phenolic acids, and amino acids being the predominant groups. PCA and hierarchical clustering revealed that metabolic variation was driven primarily by developmental stage rather than genotype. Differential metabolite profiling revealed strong stage specificity, with the callus-to-differentiation transition (LE-C vs. HE-EC) exhibiting the greatest metabolic divergence between genotypes. KEGG enrichment consistently highlighted flavonoid biosynthesis as a key differentiating pathway. Comparative analyses revealed a conserved-to-divergent pattern of metabolic regulation. During the explant-to-callus transition, both genotypes exhibited highly conserved flavonoid biosynthesis responses, with 67.5% of genes and 85.7% of metabolites showing concordant regulation (either both up-regulated or both down-regulated). In contrast, during the callus-to-differentiation transition, pronounced metabolic divergence emerged, with only 37.5% of genes and 6.7% of metabolites showing concordant regulation, and 11 flavonoid-related genes displaying opposite regulatory directions between genotypes. Notably, the HE genotype exhibited coordinated repression of CHS, CHI, F3H, UFGT, and anthocyanin biosynthesis, accompanied by decreased accumulation of naringenin and glycosylated flavonoids, along with an overall attenuation of dihydroflavonol accumulation. Conversely, the LE genotype maintained relatively active flavonoid biosynthesis and glycosylation, along with increased amino sugar and nucleotide sugar metabolism.DiscussionOur results provide comprehensive metabolomic evidence for stage-dependent metabolic reprogramming during SE in H. brasiliensis. The contrasting patterns of flavonoid metabolism between genotypes at the callus-to-differentiation transition—systematic downregulation in the HE genotype versus sustained activation in the LE genotype—are consistent with the hypothesis that a timely reallocation of metabolic flux from secondary to primary metabolism may favor somatic embryo development. This study identifies the callus-to-differentiation transition as a critical metabolic checkpoint and suggests flavonoid biosynthesis genes, particularly CHS and glycosyltransferases, as potential targets for improving SE efficiency in recalcitrant genotypes.